The classification of ways of word composition in modern German (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The issues of the classification of word composition and its types are under consideration in this article. The peculiarities of existing types of compound words have been analyzed and distinguished. The attempt to classify the types of word composition in modern German more thoroughly has been made.
Keywords: compound; word composition; defining compounds; coordinative compounds; word coalescence